Unveiling the Taxonomy and Potency of Boletellus minimatenebris (Wild Edible Mushroom) in Indonesia - Putra, Ivan Permana; Nurhayat, Oktan Dwi; Permatananda, Pande Ayu Nayakasih; Nurlita, Agessty Ika; Supratman, Lilis; Shiyam, Kania Dewi; Taridala, Sitti Aida Adha (HAYATI Journal of Biosciences, 2026)
Boletellus is a small genus of Boletaceae which is mostly distributed in the tropical area worldwide. Recently, several new species of Boletellus were introduced, including B. minimatenebris from Mexico in 2023. In 2024, a wild edible Boletellus resembling B. minimatenebris were encountered in forests and sold in traditional markets in Kendari, Indonesia. The current study was aimed at examining the taxonomical identity of our specimens and unraveling nutritional properties of this mushroom. The basidiomata was described based on the macro- and micromorphological characters. The molecular analysis and phylogenetic tree construction were performed using ITS 1/2 sequence. The proximate analyses were determined in accordance with AOAC. The combination of morphological and molecular analyses confirmed the identity of our specimens as B. minimatenebris. The indigenous people in sampling site use this species for self-consumption and sell it to local market. B. minimatenebris BO24644 is distinguished by smaller basidiomata when compared to other species within Boletellus but is larger compared to specimens from type locality. The inferred phylogenetic tree nested our specimen in the clade of B. minimatenebris from type locality (Mexico) and was a sister clade to B. aurocontextus. The proximate analysis showed low moisture and fat content, moderate fiber, high mineral presence, and a notably high protein level. In addition, the GC-MS analysis of methanolic extracts from B. minimatenebris revealed a diverse chemical profile dominated by fatty acid esters, sulphurous acid derivatives, and terpenoid. These results show the potential of B. minimatenebris BO24644 as a promising functional food.